2008
DOI: 10.1007/s10549-008-0034-1
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of adjuvant docetaxel, doxorubicin, and cyclophosphamide (TAC) for node-positive breast cancer: modeling the downstream effects

Abstract: For women with node positive BC, TAC improves DFS and OS compared to FAC and is a cost-effective adjuvant chemotherapy strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
2
13
3
Order By: Relevance
“…Our results were consistent with those from Au et al 21 , who reported a cost per qaly of $18,505.54. They used Alberta provincial costs and also based their analyses on the tac-fac study.…”
Section: Discussionsupporting
confidence: 93%
“…Our results were consistent with those from Au et al 21 , who reported a cost per qaly of $18,505.54. They used Alberta provincial costs and also based their analyses on the tac-fac study.…”
Section: Discussionsupporting
confidence: 93%
“…Economic evaluations for other docetaxel-based adjuvant chemotherapy regimens for breast cancer have also been conducted 23,[42][43][44][45][46] . Compared with fac (5-fluorouracil-doxorubicin-cyclophosphamide), tac (docetaxel-doxorubicin-cyclophosphamide) administered with and without prophylactic g-csf was found to be a cost-effective strategy in a number of jurisdictions 36,37,39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with fac (5-fluorouracil-doxorubicin-cyclophosphamide), tac (docetaxel-doxorubicin-cyclophosphamide) administered with and without prophylactic g-csf was found to be a cost-effective strategy in a number of jurisdictions 36,37,39,40 . From a Canadian health care system perspective, Au et al 42 reported cost-utility ratios of $46,003 and $18,506 per qaly gained with and without prophylactic g-csf at a 10-year horizon, and Mittmann et al 43 reported cost-utility ratios of $13,044 and $6,848 per qaly gained at a lifetime horizon. From a U.K. National Health Service perspective, Wolowacz et al 44 Compared with fec100 (5-fluorouracil-epirubicin-cyclophosphamide), fec-d (5-fluorouracil-epirubicin-cyclophosphamide-docetaxel) was also found to be a cost-effective strategy 23,46 .…”
Section: Discussionmentioning
confidence: 99%
“…This concern has led to an entirely new field of research: analysis of cost effectiveness in medicine in general and oncology specifically [3]. BCRT has, like many journals with clinical content, included manuscripts in which the cost effectiveness of a new treatment has been compared to an existing one [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Recently, though, the Editors have noticed a disturbing trend in that the submitted manuscripts appear to have been mainly or totally prepared and written by pharmaceutical companies.…”
Section: Since Its Inception Breast Cancer Research and Treatmentmentioning
confidence: 99%